2002
DOI: 10.1080/02724990244000070
|View full text |Cite
|
Sign up to set email alerts
|

Taste Aversion after Ingestion of Lithium Chloride: An Associative Analysis

Abstract: In five experiments with rats we examined the aversion established by consumption of a solution of lithium chloride (LiCl). Experiment 1 showed that consumption of LiCl established an aversion to saline (NaCl). Experiment 2 showed that the size of the aversion was reduced in rats given pre-exposure to saline (a latent inhibition effect). Experiment 3 showed that experience of a sucrose-saline compound prior to consumption of LiCl generated an aversion to sucrose (a sensory preconditioning effect). Experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 20 publications
1
32
1
4
Order By: Relevance
“…No data were recorded during the preexposure phase. As we anticipated, on the basis of the results of Loy and Hall (2002), the rats (in the LI-LO and SI-LO groups) given access to the LiCl solution in Conditioning trial 1 drank it as readily as those (in the SI-SO group) given saline. Group mean scores were 3.8 ml and 4.0 ml for the LI-LO and SI-LO groups and 3.9 ml for the SI-SO group.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…No data were recorded during the preexposure phase. As we anticipated, on the basis of the results of Loy and Hall (2002), the rats (in the LI-LO and SI-LO groups) given access to the LiCl solution in Conditioning trial 1 drank it as readily as those (in the SI-SO group) given saline. Group mean scores were 3.8 ml and 4.0 ml for the LI-LO and SI-LO groups and 3.9 ml for the SI-SO group.…”
Section: Resultsmentioning
confidence: 83%
“…The SI-SO (SO: saline taken orally) group also received injections of saline during preexposure but drank NaCl rather than LiCl in the next phase. On the basis of the results of Loy and Hall (2002), subjects in the SI-LO group can be expected to show an aversion to the NaCl solution on test and thus drink less than subjects in the SI-SO group. Subjects in the LI-LO group might also be expected to show an aversion; the question of interest was the extent to which their preexposure treatment might attenuate this aversion.…”
Section: Experiments 1a and 1bmentioning
confidence: 99%
See 2 more Smart Citations
“…In certain compound conditioning situations, CS preexposure actually attenuates the overshadowing effect that otherwise occurs as a result of compound training (Blaisdell, Bristol, Gunther, & Miller, 1998;Loy & Hall, 2002; but see Nakajima, Ka, & Imada, 1999;Nakajima & Nagaishi, 2005). In a conditioned suppression preparation with rat subjects, Blaisdell et al observed that preexposure to a CS (X) before reinforcing it in compound with a more salient CS (A) results in conditioned responding to X that is stronger than in a situation in which X is not preexposed prior to compound training.…”
mentioning
confidence: 99%